An investigation into difficulties in designing lesson plans experienced by pre-service teachers at the University of Foreign Language Studies – the University of Danang - Phan Thi Thanh Nga (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
It is indisputable that developing pre-service teachers’ lesson-planning skills plays a key role in the language teacher training program. However, lesson planning is currently inadequately evaluated as a laborious task to many pre-service teachers and they encounter a host of difficulties in tailoring a meticulous lesson plan. Since there is not much research into this subject in Vietnam, this paper is carried out with the purpose of investigating the difficulties in designing lesson plans experienced by pre-service teachers at the University of Foreign Language Studies – the University of Danang. This research employs qualitative approach of the data collected from questionnaire and semi-structured interview. The subject involves in the research are pre-service teachers majoring in English Language Teacher Education. Seventy (70) trainee teachers took part in the questionnaire at the first stage of data collection. Among these participants, at the second stage for semi-structured interview, the recording was administered to a population of ten (10) pre-service teachers who were chosen randomly with convenience. Hopefully, the research would serve as a source of reference for trainee teachers in particular and teachers of English in general.